Pengaruh Praktik Kerja Lapangan, Self Efficacy dan Hasil Belajar Terhadap Kesiapan Kerja Siswa - Farikha, Nuzulu Nuriel; Nurhidayati, Anik (Universitas Muria Kudus, 2025)
This study aims to investigate the impact of field work practice, self efficacy, and learning outcomes on students' work readiness in the motorcycle business engineering department at SMK Umar Fatah Rembang. The study took place at SMK Umar Fatah in August 2024. The population that became the focus of this study were students from the motorbike business engineering department at the school. The sample taken consisted of 132 students, with the sample selection method using purposive sampling based on two criteria, namely class XII students majoring in motorcycle business engineering at SMK Umar Fatah Rembang for the 2024/2025 school year and students who have participated in field work practices. Using 2 instrument tests, namely validity and reliability tests. Data analysis was carried out through the application of multiple linear regression with the results of the t or partial test and the determination test or R2. The research findings show that field work practice has a significant positive effect on student work readiness, while self efficacy shows an insignificant positive effect, and learning outcomes have a significant positive effect on student work readiness. The adjusted R2 value of 0.540 indicates that 54% of students' work readiness can be explained by the three independent variables, while the remaining 46% is influenced by other variables not examined in this study.